Correlation analysis of serum intestinal fatty acid binding protein, D-lactic acid and intercellular adhesion factor-1 in sepsis patients with intestinal ischemia: Serum intestinal fatty acid binding protein, D-lactic acid and intercellular adhesion factor-1 in intestinal ischemia with sepsis - Shu, Yujie; Lao, Bo; Song, Zhangzhang; Zhuang, Zhixing; Li, Hongzhang (Journal of Medical Biochemistry, 2025)
Objective: To analyze the correlations between the levels of serum intestinal fatty acid binding protein (I-FABP), D-lactic acid (D-Lac), and intercellular adhesion factor-1 (ICAM-1) in patients with sepsis complicated with intestinal ischemia‒reperfusion injury and the degree of intestinal mucosal injury and patient prognosis. Methods: A total of 236 patients with sepsis complicated with intestinal ischemia‒reperfusion injury were included in the reperfusion injury group, and 176 patients with sepsis alone during the same period were included in the sepsis group. Based on the extent of intestinal mucosal damage, individuals in the reperfusion injury group were split into three groups: mild injury (52 patients), moderate injury (116 patients), and severe injury (68 patients). The patients were further divided into a good prognosis group (188 patients) and a poor prognosis group (48 patients). The general clinical data of all patients and laboratory test indicators before and after treatment were collected and grouped for comparison. Correlation analysis was conducted via Spearman correlation analysis. Predictive value assessment was conducted via receiver operating characteristic (ROC) curves. Results: The reperfusion damage group had higher levels of I-FABP, D-Lac, ICAM-1, and IMA than the sepsis alone group, whereas the GLP-1 level was lower (P<0.05) than the sepsis alone group. Before treatment, the levels of I-FABP, D-Lac, ICAM-1 and IMA in the mild, moderate and severe injury groups increased successively, and the level of GLP-1 decreased successively (P<0.05). After treatment, the levels of I-FABP, D-Lac, ICAM-1 and IMA in the three groups of patients were all lower than those before treatment in the same group, and the levels of the above indicators in the severe injury group were all greater than those in the mild and moderate injury groups during the same period. The GLP-1 levels of the three groups of patients were all higher than those before treatment in the same group. In comparison to the mild and moderate damage groups, the severe injury group’s GLP-1 levels were lower during the same time period (P<0.05). Spearman correlation analysis revealed that the levels of I-FABP, D-Lac, ICAM-1 and IMA were positively correlated with the AGI grade, whereas the level of GLP-1 was negatively correlated with the AGI grade (P<0.05). While the level of GLP-1 was lower than that of the good prognosis group (P<0.05), the levels of I-FABP, D-Lac, ICAM-1, and IMA were higher in the bad prognosis group. The ROC curve analysis revealed that the combined predictive value of I-FABP, D-Lac, ICAM-1, IMA, and GLP-1 for poor prognosis in patients with sepsis complicated with intestinal ischemia reperfusion injury was greater than that of these five indicators alone (P<0.05). Conclusion: The levels of serum I-FABP, D-Lac, ICAM-1, IMA and GLP-1 in patients with sepsis complicated with intestinal ischemia‒reperfusion injury are closely related to the degree of intestinal mucosal injury and prognosis. The combined prediction of short-term prognosis has high clinical value.